ANALISIS DETERMINAN KEJADIAN STUNTING ANAK USIA 24-59 BULAN DITINJAU DARI STATUS BEKERJA IBU PADA KELUARGA BURUH INDUSTRI KOTA SEMARANG - Jatiningsih, Sasi Pramita; Budiono, Irwan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Stunting is a condition of short and very short nutritional status based on body length for age (PB/A) or height for age (TB/A) less than -2 standard deviations (SD) on the WHO standard growth curve. This research is an observational analytic research using quantitative research methods and cross sectional design. This research was conducted in the working area of the Bandarharjo Health Center, North Semarang from February to June 2023. The total sample in this study was 55 stunted toddlers aged 24-59 months who came from families of industrial workers. The sampling technique used total sampling according to the inclusion and exclusion criteria. Data analysis in this study used univariate, bivariate, and multivariate analysis. Bivariate analysis used the Kolmogorov Smirnov, Mann Whitney, Chi Square, and Fisher test techniques. While multivariate analysis using binary logistic regression.The results of the analysis showed that the factors that had significant differences with the incidence of stunting in toddlers aged 24-59 months in the families of industrial workers were reviewed based on the mother's working status, namely a history of exclusive breastfeeding (p = 0.002); history of complementary feeding (p = 0.005); per capita income (p = 0.003); and energy adequacy level (p = 0.014). After being analyzed multivariately, the most dominant factor in this study was the history of complementary feeding (p = 0.023; OR = 0.194).